Fundamental Studies of Metal Ion Extraction into Ionic Liquids By Macrocyclic Polyethers - (:unkn) unknown (My University, 2017)
The liquid-liquid extraction (LLX) of metal ions from aqueous media into ionic liquids (ILs) by macrocyclic polyethers has proven to be an efficient and selective, but complex approach to their separation. Partitioning in these systems has previously been described using a so-called ‘three-path’ model comprising three distinct extraction pathways: neutral complex / ion pair extraction, exchange of the IL cation for a metal-extractant complex, and exchange of the metal ion for a hydronium ion bound to the extractant. The balance of these three paths has been reported to be affected by several characteristics of the LLX system, including the structure of the IL, the stereochemistry of the extractant, and the Lewis acidity of the metal ion, among others. Qualitative trends for many of these factors have been reported, but despite the tremendous number of anion-cation combinations yielding an ionic liquid (i.e., > 108), only a single family (i.e., 1, 3-dialkylimidazolium) has been systematically studied. Evaluating the benefit (i.e., improved efficiency or selectivity), if any of employing other families of ILs as extraction solvents requires extensive partitioning studies. Consequently, the performance of most IL families remains largely unknown. Furthermore, a quantitative description of metal ion extraction from acidic media into ionic liquids is necessary before they can be considered useful extraction solvents. In general terms then, the objective of this work is to investigate several families of ionic liquids to determine whether qualitative trends reported previously represent a ‘generic’ description of metal ion extraction in IL-based systems and if these trends can be confirmed quantitatively. To this end, extraction studies employing quaternary ammonium- and N-alkylpyridinium-based ILs and alkali and alkaline earth cations have been conducted to determine if the ‘three-path’ model provides a satisfactory description of metal ion partitioning in these LLX systems. The results of these studies are consistent with those reported previously for systems employing 1, 3-dialkylimidazolium-based ILs, but they have also unexpectedly revealed a significant effect of the self-aggregation of the IL cation on extraction behavior. In an attempt to reduce the number of experimental measurements required to describe metal ion extraction into an ionic liquid, several parameters that define the hydrophobicity of an IL (e.g., hydrophilicity index, water solubility, and Dow) have been investigated and found to accurately predict extraction behavior. Lastly, a process by which to quantitatively describe the balance of pathways in an IL-based extraction system that can be used as a basis for future evaluation of ILs as extraction solvents has been developed.
Keywords: Ionic Liquids; Metal Ion Extraction